Upaya Penanganan Ilegal Fishing Di Laut Natuna Dalam Kajian Hukum Internasional - Laika Fisabilillah; Muhammad Bintang Alfath Richard (Jurnal Ilmiah Wahana Pendidikan, 2023)
Illegal fishing is still rife in Indonesian waters despite efforts to eradicate it. The potential of fishing in Indonesian waters is so great that it is often used by local and foreign entities for illegal fishing. Illegal fishing and sharing of catch abroad without proven inspection procedures has brought revenue losses to cities or states, which can be detrimental to the national economy. The main issues to be addressed in order to support the conceptual model of Fisheries without harming the sea and violating existing and sustainable regulations, that is, what factors cause fishery crimes and how to deal with them, ensuring that criminals are proportionally prevented and punished from these crimes.